Petering Out or Flaming Up? New Institutional Economics in East-Central Europe - János Mátyas Kovács (Journal of Economic Sociology, 2012)
In the paper, János Matyas Kovács reflects upon frictions in the reception of the new institutional economics in Eastern Europe. Large-scale importation of new institutional economics (NIE) was predicted at the beginning of postcommunist transformation in Eastern Europe. The institutionalist explanations seemed to be the most suitable approach in the light of deep-going institutional shifts toward capitalism. Besides textbook Marxism was vanishing while mainstream neoclassical economics was not widely spread. Under these conditions, NIE and ORDO liberalism were expected to be the best options for many scholars. Surprisingly, Eastern Europe was not flooded with the NIE concepts. The short period of NIE’s intensive development in the late 1990s was followed by its stagnation. Instead of consolidation around a unified scientific paradigm, regional economists preferred eclectic research programs, which combined a bunch of approaches. Furthermore, NIE theories encountered a strong rival — mainstream neoclassical theory. Neoclassical paradigm included a number of NIE-type solutions, allowing neoclassical economists to continue their abstract model-constructing. Thus, proponents of neoclassical economic theory did not have obvious stimuli to join new institutional economics. Nevertheless, author presumes that one cannot exclude a new upsurge in the perception and creative application of NIE ideas in the near future. Cultural compromises and the emergence of hybrid theories can give a way toward a smooth evolution of new institutionalism. Using results of a research project carried out in eight countries, János Kovács gives a comprehensive picture of this peculiar transformation in economic and social sciences.